2019
DOI: 10.20517/2394-4722.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study for distinguishing basal cell carcinoma from normal human skin tissues using visible resonance Raman spectroscopy

Abstract: Aim:The aim of the study is to test visible resonance Raman (VRR) spectroscopy for rapid skin cancer diagnosis, and evaluate its effectiveness as a new optical biopsy method to distinguish basal cell carcinoma (BCC) from normal skin tissues. Methods:The VRR spectroscopic technique was undertaken using 532 nm excitation. Normal and BCC human skin tissue samples were measured in seconds. The molecular fingerprints of various native biomolecules as biomarkers were analyzed. A principal component analysis -support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…46 These observations are in good agreement with changes of tryptophan contents in human brain malignant meningioma and gliomas tissues 10 and skin basal cell carcinoma tissues. 19 The molecular biomarker of tryptophan provides a potential approach to diagnose metastatic brain cancerous tissues and other cancers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 These observations are in good agreement with changes of tryptophan contents in human brain malignant meningioma and gliomas tissues 10 and skin basal cell carcinoma tissues. 19 The molecular biomarker of tryptophan provides a potential approach to diagnose metastatic brain cancerous tissues and other cancers.…”
Section: Resultsmentioning
confidence: 99%
“…This result is well consistent with the previous reports of Raman spectra of glioblastoma multiforme (GBM) and basal cell carcinoma ex vivo. 10,18,19 The ratios serve as a key approach to predict the metastatic potential of brain cancer using VRR spectroscopy analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the fingerprint and high‐wavenumber regions (FP/HW) in the GA‐PLS‐LDA algorithm had an accuracy, sensitivity, and specificity of 96.76, 87.78, and 100%, respectively—higher than the analogous blood test which may be attributable to the simultaneous unique advantages of both FP and HW Raman tissue spectra (Žuvela et al, 2019). Recent work successfully used resonance Raman techniques (RRS) for brain tumor biopsies (Zhou et al, 2018, 2019), skin cancer detections (Liu et al, 2019), and breast cancer subtype separation (Bendau et al, 2020). Using spontaneous RS to scan colon cells from patients, a k‐means clustered image‐trained support vector machine was able to diagnose the samples as having Ulcerative Colitis, Crohn's disease, or no irritable bowel disease (IBD).…”
Section: Modality Of Raman Imaging On Tissuesmentioning
confidence: 99%
“…The study presented by Zaichick et al [10] showed that contents of several chemical elements were drastically different between thyroid malignant tumors and normal thyroid tissues. Finally, Liu et al [11] reported the results of using visible resonance Raman spectroscopy for rapid skin cancer diagnosis.…”
Section: Introduction To This Special Issue: "Biomarker Discovery Andmentioning
confidence: 99%